2000
DOI: 10.1177/000348940010901111
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neutrophil Elastase in Endotoxin-Induced Mucus Hypersecretion in Rat Nasal Epithelium

Abstract: In the present study, hypertrophic and metaplastic changes of goblet cells were induced in rat nasal epithelium by intranasal instillation of endotoxin or elastase. A significant increase in the amount of intraepithelial mucosubstance was observed after 24 hours during 3 days of instillation. The elastase-induced mucus production was not inhibited in neutrophil-depleted rats, but the endotoxin-induced change was significantly inhibited. Intranasal instillation of the neutrophil elastase inhibitor ONO-5046 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Previous in vivo and in vitro studies have shown that LPS stimulates mucin secretion and upregulates the mucin gene. [36][37][38] Consistently, our data revealed that LPS induces excessive synthesis and secretion of mucin by LS174T cells. Besides, ICA and pICA also restore mucin synthesis and secretion to normal levels.…”
Section: Discussionsupporting
confidence: 85%
“…Previous in vivo and in vitro studies have shown that LPS stimulates mucin secretion and upregulates the mucin gene. [36][37][38] Consistently, our data revealed that LPS induces excessive synthesis and secretion of mucin by LS174T cells. Besides, ICA and pICA also restore mucin synthesis and secretion to normal levels.…”
Section: Discussionsupporting
confidence: 85%
“…Neutrophil elastase inhibitor ONO 5046 partially inhibited LPSinduced change, and elastase-induced mucus production was not inhibited by neutrophil depletion (28). These results indicate that neutrophil, especially neutrophil elastase, is an important mediator of LPS-induced mucus production and that the in vivo effects of 14-member macrolides may be partly caused indirectly through the suppression of neutrophil infiltration.…”
Section: Discussionmentioning
confidence: 77%
“…This degranulation can be explained by the release of elastase from the azurophilic granules of heterophils in the regions where goblet cells are degranulating. Elastase is a powerful secretagogue on the glands and goblet cells of the airways [43]. …”
Section: Discussionmentioning
confidence: 99%